EXPLORING THE CHENNAMANGALAM SAREES OF KERALA - Nair, Kavya M; S., Greeshma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India’s economy is heavily reliant on the fashion industry, which boasts a rich array of traditional textiles. Among these, the Chennamangalam sarees stand out as a vivid representation of the nation’s heritage. Hand-loomed in the village of Chennamangalam in Kerala, these sarees feature intricate designs and vibrant hues, showcasing the creative and technological prowess passed down through generations. Crafted by skilled artisans using locally sourced fabrics, these sarees are renowned for their stunning designs and sustainable materials, preserving traditional craftsmanship and environmentally responsible methods. They appeal to style enthusiasts seeking a blend of modernism and heritage, making them highly sought-after both domestically and internationally. By combining sustainability with style and heritage with innovation, Chennamangalam sarees are poised to make a significant impact on the global market for Indian textiles. This paper thoroughly examines Chennamangalam sarees, focusing on their rich history, intricate weaving techniques, and cultural significance. It also explores their entry into the global market, the support systems that sustain the craft, and the current dynamics of supply and demand. Providing valuable insights for participants in the textile industry, this study offers a comprehensive review of the opportunities and challenges facing Chennamangalam sarees in the future.